The Efficacy in Predicting Risk of Injury in Collegiate Basketball Players : Functional Movement Screening vs. Traditional Pre-Participation Examination. - Gibson, Kyle M.; Stuewe, Katherine A.; O'Brien, Corey W. (My University, 2009)
Historically, the standard pre-participation examination (PPE) denies 0.3% ? 1.3% of athletes, and alone may not adequately identify those individuals at-risk for injury. Kiesel, Pliskey, and Voight recently reported that a pre-season assessment of fundamental movement patterns in professional football players could predict risk of serious injury. This study tested college basketball players to address two questions: 1) are there differences between the traditional PPE and the functional movement screen (FMS) in the number of athletes cleared for participation and 2) is the pre-season FMS score associated with an increased risk of injury.
Color poster with text, images, and tables (Spring 2009)
Keywords: College athletes--Examinations; Basketball injuries--Risk assessment; Human mechanics--Testing; Posters